The impact on auditors of non-compliance with laws and regulations - Shagaran Rathnasamy; Vishad Mahabeer (Jurnal Akuntansi dan Auditing Indonesia, 2021)
This article clarifies and expands on the implications of the pronouncement: Non-Compliance of Laws and Regulations (NOCLAR), on Registered Auditors and Professional Accountants in South Africa. NOCLAR was introduced to assist legislative reporting obligations and strengthen professionalism and law coherency. The study clarifies the implications the IRBA and SAICA Codes of Professionals Conduct have on Accountants and Auditors and the course of action required if, all prior equivocal guidelines fail to address an illegality. Due to the relative infancy in the application of the NOCLAR amendment in South Africa, this study adopted a qualitative research methodology by critical review and analysis of commentaries, guidelines and application of the amendment by South African Accountants, Auditors and Academics. The study found that non-adherence to the amendment results in 3 key repercussions for both company and/or the Accountant and Auditor: Reputational damage, Loss of current clientele and future business opportunities and criminal charges.